Feasibility assessment for ramp metering in Northern Ireland - Maxwell, B; Day, P (12th IEE International Conference on Road Transport Information & Control - RTIC 2004, 2004)
Ramp metering is a traffic management tool that has been widely adopted in continental Europe to improve motorway flow at times of peak congestion. Recently its use has also been the subject of a trial conducted by the Highways Agency in England on the M3 and M27 motorways and sites previously adopted on the M6 are being re-assessed to identify its benefit. Elsewhere in the UK it has been implemented as part of a complimentary route management strategy on an approach to Glasgow. Roads Service is the sole road authority in Northern Ireland, responsible for approx 25000 kms of all classes of road including approx 110 kms of motorway. The paper describes the consideration given to the use of intelligent transport systems (and ramp metering in particular); the scheme assessment process that was adopted; an overview of the results generated by the assessment; the reasons as to why public transport became a key scheme concern and a summary of the lessons learnt through an appraisal of emerging technology.